Rethinking how we educate our future physicians: The Queen’s-Lakeridge Health Medical Degree Family Medicine program: An innovative approach to medical education - Piliotis, Eugenia; Turnnidge, Jennifer; McGuire, Cailie S; Dalgarno, Nancy; Sanfilippo, Anthony J; Balasubramaniam, Arun; Gibson, Michelle; Green, Michael; Watson, Shayna; Fitzpatrick, Renee; Wax, Randy S; McHattie, Heidi; et al. (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2026)
Canadian healthcare, particularly family medicine, is experiencing a capacity crisis. To address this challenge, systems-level reform is required. Specific to medical education, there is an urgency for educational institutions to prepare the next generation of physicians to meet Canadians’ healthcare needs. This will require not only the expansion of the number of physicians trained, but consideration of the specialty mix and types of practice those physicians are prepared to undertake. Building on an existing collaborative partnership, the Queen’s-Lakeridge Health Doctor of Medicine - Family Medicine Program (QLH MD FM) launched in 2023. This initiative is designed to address the needs of Canadians through purposeful recruitment and the development of learners interested in, and committed to, careers in family medicine. This paper shares the experiences of the QLH MD FM team, and the steps taken in conceptualizing and implementing this educational initiative. A program description is provided, focusing on the six program pillars: (a) admissions, (b) curriculum, (c) faculty and staff engagement, (d) community engagement, (e) infrastructure and supports, and (f) learner experience. The QLH MD FM Program is an innovative approach to medical education that emphasizes an authentic focus on addressing the complex healthcare needs of individuals and their communities.